Response of diminazene-resistance and diminazene-susceptible Trypanosoma congolense to treatment with diminazene when occuring as a mixed infection in goats - Burudi, E.M.E.; Peregrine, A.S.; Majiwa, Phelix A.O.; Mbiuki, S.M.; Murphy, N.B. (1994)
A study was carried out to determine whether a drug-resistant trypanosome population could influence the survival of a drug-sensitive population in mixed infections in goats. To identify both populations during the course of a mixed infection, a system for distinguishing them was developed; using a nucleotide sequence of cDNA that was derived from Trypanosoma congolense ILNat 3.3 (IL 1616), a pair of 20-mer primers was designed which, in a PCR, amplified a 900-bp sequence from the diminazene-senstive trypanosome, T. congolense IL 1180, but not the diminazene-resistant trypanosome, T. congolense IL 3247. The PCR technique detected 100 pg of IL 1180 DNA when mixed with 25 ng of total genomic DNA of IL 3274 as determined by gel electrophoresis and ethidium bromide-staining of the PCR products. Using the 900-bp PCR product as a 32 P-labelled probe on Southern blots, the sensitivity was increased 100-fold. Three groups of five goats each were infected with IL 1180 (group A.), IL 3274 (group B) or both clones simultaneously (group C), and treated with diminazene aceturate at a dose of 7.0 mg/kg body weight following detection of trypanosomes. Three other groups of three goats each were similarly infected and kept as untreated controls. All group A animals were cured, while all in group B and four animals in group C relapsed. Trypanosomes were harvested from all animals at regular intervals up to 60 days post treatment. Using the PCR techniques, IL 1180 DNA could not be detected in any post-treatment trypanosome DNA sample. It therefore appeared, on the basis of the sensitivity of the DNA detection systems used, that IL 1180 is unable to survive treatment with diminazene aceturate when mixed with IL 3274 in goats.